(untitled) (Communications in Mathematical Research, 2021)
In this paper, we propose and analyze a full-discretization spectral approximation for a class of Cahn-Hilliard equation with nonconstant mobility. Convergence analysis and error estimates are presented and numerical experiments are carried out.